MEDIATION: AN ALTERNATIVE FOR CONFLICT RESOLUTION IN PUBLIC ADMINISTRATION (REMUNOM, 2023)
This article addresses mediation as a means of conflict resolution within the Public Administration. The analysis was based on the following problematic perspective: what is mediation as an alternative to jurisdiction in the resolution of conflicts involving the Public Administration? To answer the proposed problem, the work had as general objective is to analyze mediation as an alternative for conflict resolution in Public Administration. The methodology used was the literature review, qualitative and explanatory. The results showed that mediation is an activity performed by an impartial third party without decision-making power, chosen or accepted by the parties, which assists and stimulates to identify or develop consensual solutions to controversy. Thus, the parties themselves are responsible for resolving the conflict, while the mediator helps them overcome the barriers that prevent the resolution of the dispute. It was concluded that mediation in the solution of conflicts involving the Public Administration leaves behind the rigidity and formality imposed by the State and enables the restoration of dialogue between the parties involved in the conflict. In addition, the possibility of using mediation in the resolution of conflicts between individuals and legal entities under public law allows the construction of peaceful solutions and respect for constitutional fundamental rights.